A Comorbidity Model of Myocardial Ischemia/Reperfusion Injury and Hypercholesterolemia in Rat Cardiac Myocyte Cultures - Makkos, András; Szántai, Ágnes; Pálóczi, János; Pipis, Judit; Kiss, Bernadett; Poggi, Paola; Ferdinandy, Péter; Chatgilialoglu, Alexandros; Görbe, Anikó (Frontiers in Physiology, 2020)
Introduction: The use of comorbidity models is crucial in cardioprotective drug development. Hypercholesterolemia causes endothelial and myocardial dysfunction, as well as aggravates ischemia/reperfusion (I/R)-induced myocardial injury. Endogenous cardioprotective mechanisms against I/R are impaired in hyperlipidemic and hyperglycemic in vivo animal models. Therefore, our aim was to develop a medium throughput comorbidity cell-based test system of myocardial I/R injury, hypercholesterolemia and hyperglycemia that mimics comorbidity conditions. Methods: Cardiac myocytes isolated from neonatal or adult rat hearts were cultured in control or in three different hypercholesterolemic media with increasing cholesterol content (hiChol) or hiChol + hyperglycemic medium, respectively. Each group was then subjected to simulated ischemia/reperfusion (SI/R) or corresponding normoxic condition, respectively. Cholesterol uptake was tested by Filipin staining in neonatal cardiac myocytes. Cell viability, total cell count and oxidative stress, i.e. total reactive oxygen species (ROS) and superoxide level were measured by fluorescent assays. Results: Neonatal cardiac myocytes took up cholesterol from the different hiChol media at a concentration-dependent manner. In normoxia, viability of hiChol neonatal cardiac myocytes was not significantly changed, however, superoxide levels were increased as compared to vehicle. After SI/R, the viability of hiChol neonatal cardiac myocytes was decreased and total ROS level was increased as compared to vehicle. HiChol combined with hyperglycemia further aggravated cell death and oxidative stress in normoxic as well as in SI/R conditions. Viability of hiChol adult cardiac myocytes was significantly decreased and superoxide level was increased in normoxia and these changes were further aggravated by SI/R. Conclusion: HiChol rat cardiac myocytes showed reduction of cell viability and increased oxidative stress, which were further aggravated by SI/R and with additional hyperglycemia. This is the first demonstration that the combination of the current hypercholesterolemic medium and SI/R in cardiac myocytes mimics the cardiac pathology of the comorbid heart with I/R and hypercholesterolemia.